91.6k views
18 votes
Can you solve (x-2)(x+3) = 5 by solving x - 2 =5 and x + 3 =5? Why or why not?

1 Answer

8 votes

Answer:

no we cannot because when we solve x-2=5 it gives x=7 and x+3=5 gives x=2 if we place the x value as 7 then it does not justify (x-2)(x+3)=5, if we put x= 2 then again it does not justifies (x-2)(x+3)=5

Explanation:

x-2=5

x=5+2

x=7

x+3=5

x=5-3=2

putting x=7 in given equation

(7-2)(7+3) is not equal to 5

putting x=2 in given equation

(2-2)(2+3) is not equal to 5

that's why we can't solve

User Esbanarango
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.